Kate in waiting - Albertalli, Becky (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
Best friends Kate Garfield and Anderson Walker share a love of theater and crushes on the same guys, but when one of their long-distance crushes shows up at their school, real feelings might end their friendship
Keywords: Jugendbuch; Love is Queer; Liebeskomödie Buch; Schauspiel; Kate Garfield; Anderson Walker; Liebesgeschichte; Young Adult Liebesromane; Roman Freundschaft; New Romance Buch; young adult romance; Beste Freunde; Queerness; New Adult Romane; Becky Albertalli; Theater; romantische Liebesromane; New Adult Bücher; LBGT+; Schauspieler; Love Simon; LGBTQ Romane; romantische Komödie; New Adult Liebesroman deutsch; Schauspielerin; Schauspielschule; Romance; Liebesroman New Adult; Roman USA; Romane LGBT; New Adult; College; Young Romance; amerikanische Romane; Young Adult Bücher; Matt Olsson; Boys Love; Romane Liebe; humorvolle Liebesromane; High school students / Fiction; Gay teenagers / Fiction; Theater / Fiction; Friendship / Fiction; Young adult fiction; YOUNG ADULT FICTION / Romance / Contemporary; YOUNG ADULT FICTION / LGBTQ+; YOUNG ADULT FICTION / Performing Arts / Theater & Musicals; Young adult works; Novels; Erzählende Literatur: Gegenwartsliteratur ab 1945; Freundschaft; Jugend; Liebe; High school; Schultheater; Homosexualität